(untitled) (American Journal of Islam and Society, 2002)
"The strength of America is in its diversity, and this diversity includes the Islamic component, which is part of the American mainstream now." So proclaimed ISNA secretary general Sayyid M. Syeed while inaugurating the sixth annual ISNA Islam in America Conference, which is now part of the American academic calendar. Held in Chicago on July 5-7, four conferences were featured: Islam in America, Islam among Latino Americans, Islam in American Prisons, and Muslim Refugee Resettlement in America. The mainstream American media was there in full to cover these events. l n his inaugural address, Syeed said that Muslims must continue to shape their public identity as they further integrate into mainstream American society. He added that while public perceptions about Muslims and Islam have improved over the last 30 years, there is still work to be done. He stated that ISNA will continue to serve Muslim Americans and promote understanding among all Americans, and that INSA has received a federal faith-based initiative grant for a project. Mary Ann Peters, American ambassador to Bangladesh, remarked in her keynote address that America derives its strength from diversity and stressed that there is no acceptable level of intolerance in America. She informed the audience that she had reached out to over 2,000 Bangladeshi religious leaders to promote womens’ rights in their country, and that pro moting democracy overseas serves American interests. She would like to see better relations between the U.S. and Muslim countries, and mentioned that the American government has accepted her suggestion of regular exchanges of religious scholars between the two countries. Shaikh Hamza Yusuf focused on the Prophet’s conduct and reminded everyone that he never repaid persecution, insults, or injury with anger or in kind. Addressing the mainstream media’s treatment of Muslims, Yusuf said that instead of simply criticizing the media, Muslims must form an organization similar to the Anti-Defamation League that could correct and inform their detractors. Dr. David Schwartz, another keynote speaker who recently retired as religious services administrator for the Federal Bureau of Prisons, said that Islam is a positive element in inmates’ lives. He vehemently rejected the insinuation that American prisons are being used as ...